Predictors of severe head injury in tertiary centre - Rajendra Shrestha (Romanian Neurosurgery, 2020)
Introduction: Severe head injury (SHI) is associated with a high mortality and morbidity rate and is one of the leading causes of death in intensive care units. The aim of this study was to identify predictors of hospital outcome and mortality in ICU admitted SHI patients and to estimate their impact.